“Pengaruh Pajak dan Retribusi Daerah Terhadap Pertumbuhan Ekonomi dengan Kemandirian Daerah Sebagai Variabel Mediasi pada Kabupaten/Kota Provinsi Nusa Tenggara Barat Tahun 2017-2023” - Dima Dwiyana Halil; Baiq Ismiwati; Iwan Harsono (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
Regional economic growth is highly dependent on the capacity of local governments to manage their own revenues, particularly through the optimization of local taxes and levies. However, in West Nusa Tenggara Province, the level of regional independence still faces challenges due to the dominant role of transfer funds from the central government in the regional revenue structure. This study aims to analyze the effect of local taxes and levies on economic growth with regional independence as an intervening variable. This study uses a quantitative approach with an associative method and utilizes secondary data sourced from government financial reports. There are 70 observations in this study obtained from panel data of districts/cities in West Nusa Tenggara Province during the research period. Data analysis was performed using path analysis with the help of EViews software, and the regression model used was the Fixed Effect Model (FEM). Hypothesis testing included t-tests, F-tests, adjusted R-squared, and Sobel tests to examine the mediating role. The results showed that local taxes had a significant effect on regional autonomy and economic growth. Local levies did not have a significant effect on regional autonomy but had a significant effect on economic growth. Regional autonomy did not have a significant effect on economic growth. Based on the Sobel test, the results show that regional autonomy is unable to mediate the influence of regional taxes and levies on economic growth. This finding indicates that regional economic growth is still more influenced by factors other than regional fiscal autonomy.